Diagnostic Efficiency of Caregiver Report on the SCARED for Identifying Youth Anxiety Disorders in Outpatient Settings. (21st December 2018) - Van Meter, Anna R.; You, Dokyoung S.; Halverson, Tate; Youngstrom, Eric A.; Birmaher, Boris; Fristad, Mary A.; Kowatch, Robert A.; Storfer-Isser, Amy; Horwitz, Sarah M.; Frazier, Thomas W.; Arnold, L. Eugene; Findling, Robert L.; et al.
Abstract : This study investigated the diagnostic and clinical utility of the parent-rated Screen for Child Anxiety Related Emotional Disorders (SCARED-P) for detecting youth anxiety disorders. Youth ages 6 to 12 years, 11 months were recruited from 9 outpatient mental health clinics ( N  = 707). Consensus diagnoses were based on semistructured interviews (Schedule for Affective Disorders and Schizophrenia for School-Age Children) with youth and caregivers; 31% were diagnosed with at least one anxiety disorder. Caregivers completed the SCARED-P to describe youth anxiety levels. SCARED-P scores were not considered during the consensus diagnoses. Areas under the curve (AUCs) from receiver operating characteristic analyses and diagnostic likelihood ratios (DLRs) quantified performance of the SCARED-P total score and subscale scores (generalized anxiety disorder and separation anxiety disorder). SCARED-P total scores had variable efficiency (AUCs = .69–.88), and Generalized Anxiety Disorder and Separation Anxiety subscale scores were excellent (AUCs = .86–.89) for identifying specific anxiety disorders. Optimal subscale cutoff scores were computed to help rule in (DLRs = 2.7–5.4) or rule out (DLRs < 1.0) anxiety disorders among youth. Results suggest that the Generalized Anxiety Disorder and Separation Anxiety SCARED-P subscales accurately identify their respective matched diagnoses. DLRs may aid clinicians in screening for youth anxiety disorders and improve accuracy of diagnosis.